Pterygosomatidae and Trombiculidae mites infesting Tropidurus hispidus (Spix, 1825) (Tropiduridae) lizards in northeastern Brazil - Delfino, M. M. S.; Ribeiro, S. C.; Furtado, I. P.; Anjos, L. A. [UNESP]; Almeida, W. O. (Instituto Internacional de Ecologia, 2011)
No presente estudo foi analisado o parasitismo do lagarto Tropidurus hispidus pelos ácaros Geckobiella sp. e larvas de Eutrombicula alfreddugesi em uma área na Chapada do Araripe (07° 16' S e 39° 26' W), região sul do Estado do Ceará, Brasil. Dos 56 lagartos coletados (26 fêmeas, 27 machos, e 3 juvenis), 40 (prevalência total de 71,42%) estavam infestados por ácaros. Entre os sites de infestação, as bolsas de ácaros foram os mais infestados pelas larvas de E. alfreddugesi, enquanto Geckobiella sp. foi encontrado distribuído uniformemente sob as escamas por todo o corpo dos hospedeiros. Os espécimes fêmeas de T. hispidus parasitados por E. alfreddugesi tinham uma infestação média de 8,57 ± 3,63, 1-27, enquanto os machos tinham uma média de infestação de 11,90 ± 2,63, 1-25. Os espécimes fêmeas parasitados por Geckobiella sp. tinham uma infestação média de 5,91 ± 2,28, 1-25, enquanto que os machos tinham uma infestação média de 5,43 ± 1,52, 1-23. Sete espécimes estavam também infestados por ovos e formas imaturas de ácaros não identificados (infestação média de 2,28 ± 0,89, 1-7). Não houve diferenças significativas entre a prevalência total de ácaros em machos (70,4%) e fêmeas (65,4%) adultas. As médias dos tamanhos corporais não influenciaram as taxas de infestação. A intensidade de infestação média por E. alfreddugesi (10,2 ± 8,7) foi significativamente maior do que a encontrada para Geckobiella sp. (5,9 ± 6,8). T. hispidus constitui um novo registro de hospedeiro para ácaros do gênero Geckobiella.

Parasitism of the lizard Tropidurus hispidus by Geckobiella sp. and by larvae of Eutrombicula alfreddugesi was examined in a mountainous area in Chapada do Araripe (07° 16' S and 39° 26' W), southern Ceará State, Brazil. of the 56 lizards collected (26 females, 27 males, and 3 juveniles), 40 (total prevalence of 71.42%) were infested by mites. Mite-pockets were the sites most heavily infested by E. alfreddugesi larvae, while Geckobiella sp. was found uniformly distributed under scales over the host's entire body. The female specimens of T. hispidus parasitised by E. alfreddugesi had an average infestation rate of 8.57 ± 3.62, 1-27, while the males had an average infestation rate of 11.90 ± 2.63, 1-25. The female specimens parasitised by Geckobiella sp. had an average infestation rate of 5.91 ± 2.28, 1-25, while the males had an average infestation rate of 5.43 ± 1.52, 1-23. Seven specimens were also infested by eggs and immature forms of unidentified mites (average 2.28 ± 0.89, 1-7). There were no significant differences between the total prevalence of mites on adult male (70.4%) and adult female (65.4%) lizards. The body sizes of the hosts did not influence their infestation rates. The average infestation intensity by E. alfreddugesi (10.2 ± 8.7) was significantly greater than the average infestation intensity by Geckobiella sp. (5.9 ± 6.8). T. hispidus is the new host record to Geckobiella mites.
Ácaros Pterygosomatidae e Trombiculidae infestando lagartos Tropidurus hispidus (Spix, 1825) (Tropiduridae) no nordeste do Brasil
Keywords: ácaros; Eutrombicula; Geckobiella; lagartos; Tropidurus; mites; Eutrombicula; Geckobiella; lizards; Tropidurus